Comparative Analysis of Trust in Financial Institutions Across four Provinces in Pakistan - Aslam, Aribah; Ghouse , Ghulam (Audit and Accounting Review, 2023)
Trust in financial institutions (ToF) is considered essential for an effective financial system, yet, little has been explored regarding what determines them, particularly in the case of Pakistan. By using World Values Survey data (wave 7), large cross-provincial differences are observed for the trust on banks, which confirmed the influence of several socio-demographic indicators. The findings indicate that men tend to trust banks more than women in most cases and trust in banks tends to increase with income, but not in every province. However, it decreases with age in provinces like Balochistan, and media and internet access bring novel results for the trust in financial institutions. Additionally, trusting religious and political institutions, such as trust in government or civil wars, and economic values may affect the trust in financial institutions too. Therefore, the current study suggests to policymakers that a uniform strategy may not work equally well in boosting trust in financial institutions (ToF) across all provinces of Pakistan. However, media literacy and financial education can be prioritized, particularly in areas with lower educational attainment, which could be instrumental in fostering confidence in banks.